Global corruption : money, power and ethics in the modern world - Cockcroft, Laurence (London : |b I.B. Tauris, 2014)
Corruption has played a pivotal role in determining the current state of the world - from mass poverty in developing countries, to the destruction of natural resources and to the erosion of trust in political parties. Laurence Cockcroft here argues that corruption has to be seen as the result of the interplay between elite 'embedded networks', greed and organised crime. He shows how the growth of corruption has been facilitated by globalisation, the integration of new and expanding markets into the world economy, and by the rapid expansion of 'offshore' financial facilities. These facilities provide a home to largely unregulated pools of finance derived from personal fortunes, organised crime and pricing malpractice in international trade. By identifying the main drivers of corruption world-wide and analyzing the current action to control them, this book suggests ways in which the problems caused by corruption can be addressed and ultimately prevented.
1. What is Corruption? -- 2. The Corrosive Power of Corruption -- 3. Secret Trades -- 4. Victims of Corruption -- 5. Constant Values, Changing Standards -- 6. Why Now? -- 7. What Drives Corruption Forward? -- 8. The Long March: Is There Progress? -- 9. Key Roadblocks -- 10. Corruption and Global Warming -- 11. The People's Voice -- 12. Shaping the Future.
Originally published: 2012.
economic&political bookfair2015
Includes bibliographical references and index.
Keywords: Corruption; Political corruption -- Economic aspects; Wealth -- Moral and ethical aspects; Corruption